2007
DOI: 10.1007/s00410-007-0236-2
|View full text |Cite
|
Sign up to set email alerts
|

The importance of talc and chlorite “hybrid” rocks for volatile recycling through subduction zones; evidence from the high-pressure subduction mélange of New Caledonia

Abstract: The transfer of fluid and trace elements from the slab to the mantle wedge cannot be adequately explained by simple models of slab devolatilization. The eclogite-facies mélange belt of northern New Caledonia represents previously subducted oceanic crust and contains a significant proportion of talc and chlorite schists associated with serpentinite. These rocks host large quantities of H 2 O and CO 2 and may transport volatiles to deep levels in subduction zones. The bulk-rock and stable isotope compositions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
116
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 103 publications
9
116
0
Order By: Relevance
“…Recent studies of subduction zone mélanges have revealed that significant fluid flow and fluid-rock interaction took place along the slab-mantle interface (Bebout and Barton 1989, 2002Grossman 1989, 1993;King et al 2003King et al , 2006King et al , 2007Breeding et al 2004;Marschall et al 2006;Spandler et al 2008;Miller et al 2009;Penniston-Dorland et al 2010, 2012. The mélanges represent tectonic and metasomatic mixing of sedimentary, mafic, and ultramafic rocks along the interface region at the contact between the subducting slab and the mantle wedge.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of subduction zone mélanges have revealed that significant fluid flow and fluid-rock interaction took place along the slab-mantle interface (Bebout and Barton 1989, 2002Grossman 1989, 1993;King et al 2003King et al , 2006King et al , 2007Breeding et al 2004;Marschall et al 2006;Spandler et al 2008;Miller et al 2009;Penniston-Dorland et al 2010, 2012. The mélanges represent tectonic and metasomatic mixing of sedimentary, mafic, and ultramafic rocks along the interface region at the contact between the subducting slab and the mantle wedge.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, fluids in the subduction zone may originate from (I) the partly serpentinised, subducted mantle peridotite underneath the oceanic crust (Hyndman and Peacock, 2003;Ranero et al, 2003), (II) the altered oceanic crust (AOC; e.g. Becker et al, 2000;John et al, 2008;Peacock, 1993), (III) subducted marine sediments (Plank and Langmuir, 1993;Rüpke et al, 2002), and (IV) the mélange zone of the slab-wedge interface (Bebout, 2007;King et al, 2006;Spandler et al, 2008). Fluids circulating in the subduction zone may inherit the M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…The patterns ranging from slightly concave to flat in the middle and heavy REE are similar to the serpentinites derived from oceanic peridotites and those infiltrated by basaltic melts of Peltonen and Kontinen (2004). The negative Ce and Eu anomalies may indicate hydrothermal interactions, weathering and serpentinization, all of them caused by oceanic waters (D'Orazio et al 2004;Spandler et al 2008;De Hoog et al 2009). …”
Section: Element Mobilitymentioning
confidence: 89%